Human Resources Implementation at Imported Beef Supplier Startup Meat Tech - Anandaputri, Elisabet; Syah, Tantri Yanuar Rahmat; Kustiawan, Unggul; Nofierni, Nofierni (Journal La Bisecoman, 2025)
Middle-class Horeca in large metropolitan cities such as Jakarta, Bogor, Depok, Tangerang, and Bekasi are concerned with the quality of products and services offered by suppliers. PT Meat Tech as an imported beef supplier is concerned with these customer needs to increase consumer satisfaction. However, to create good product and service quality, companies need to manage their resources such as operational management, human resources, marketing, and finance. By qualitative approach, this research specifically reviews at how the short-term to long-term planning of human resources in an imported beef supplier company runs according to the strategy set by the company. The findings of this study are that Meat Tech focuses on managing employee performance and employee commitment in their early stage as a form of HR integration in business strategy, which is Product Development. Meat Tech focuses on managing employee satisfaction and motivation but still in accordance with company targets to meet customer needs.